KEPADATAN POPULASI KUTU DAUN (Aphis craccivora Koch) PADA TANAMAN KACANG PANJANG DI KELURAHAN KURANJI KECAMATAN KURANJI PADANG - Febriyanti, Febriyanti (IAIN Batusangkar, 2010)
Long peanut is one of the sources of protein which is easy to develop in every region. The problem of increasing the production of Long peanut is the existence of pest that destroys Long peanut. Pestwhich attack Long peanut is Aphis craccivora. In relation to that, it has been done a research about the population of Aphis craccivora of Long peanut in regency of Kuranji, Kuranji district,Padang. This research had been done on Mey 2007 in a garden of a farmer. This research used descriptive method, that is the observation directly to the field, and the data collection used Chemical Knock Down technique. Identification is done in the Laboratory of HPT department, Agriculture faculty,University ofAndalas,Padang. From this research, it is found that the population of Aphis craccivora is 83, 62 per plant. The population of Aphis craccivora is above the economic line.Key words: population, long peanut, Aphis craccivora, density